Evaluation of Structural Mitigation Effort for Flood Control in Rongkong River - Dendy Permana; Mohammad Farid; Joko Nugroho; Irfan Sudono; Nana Nasuha Djuhri (Jurnal Teknik Sipil, 2022)
Abstract. One of the alternative flood structural mitigation planned for Rongkong River is the construction of embankments and river normalization. However, river normalization has a weakness where the widening of the cross section of the river can cause an increase in sedimentation. The purpose of this study is to examine the effectiveness of the planned flood control in reducing flood runoff using the flood overflow hydraulic model. Rongkong basin was divided into 14 subbasin to create a distributive model. Design rainfall was analyzed using frequency distribution analysis with GEV method at various return period. Flood discharge was analyzed using HEC-HMS software with the SCS and Snyder methods on the 20-year return period. Hydraulic modelling was analyzed using HEC-RAS 1D with unsteady flow condition under existing and design cross section. Based on the results of flood modeling with a flood discharge Q20 of 1,046.78 m3/s resulted in a flood reduction of 100% and an increase in the average flow velocity of 18% from 1.82 m/s to 2.14 m/s. The use of Q20 as a design flood discharge in the normalization plan and construction of the Rongkong River embankment is considered too large because it causes construction costs to be very expensive. It is recommended to use Q10 in accordance with the regulation of the Ministry of Public Works and Housing, which is stated that the flood design for embankments of the river near the regency/city capital area must be able to pass the flood discharge of Q10 – Q20. It is needed to conduct a design review of the plan of normalization and construction of the embankment. Keywords: Flood control, river morphology, hydraulic modelling, HEC-HMS, HEC-RAS Abstrak Salah satu alternatif mitigasi struktural banjir yang direncanakan untuk Sungai Rongkong adalah pembangunan tanggul dan normalisasi sungai. Namun normalisasi sungai memiliki kelemahan dimana pelebaran penampang sungai dapat menyebabkan peningkatan sedimentasi. Tujuan dari penelitian ini adalah untuk menguji efektivitas pengendalian banjir yang direncanakan dalam mengurangi limpasan banjir dengan menggunakan model hidraulik limpasan banjir. DAS Rongkong dibagi menjadi 14 Sub DAS untuk membuat model secara distributif. Curah hujan rencana dianalisis menggunakan analisis distribusi frekuensi dengan metode GEV pada berbagai periode ulang. Debit banjir dianalisis menggunakan software HEC-HMS dengan metode SCS dan Snyder pada kala ulang 20 tahun. Pemodelan hidraulik dianalisis menggunakan HEC-RAS 1D dengan kondisi aliran tidak tunak pada penampang eksisting dan rencana. Berdasarkan hasil pemodelan banjir dengan debit banjir Q20 sebesar 1.046,78 m3/s menghasilkan reduksi banjir sebesar 100% dan peningkatan kecepatan aliran rata-rata sebesar 18% dari 1,82 m/s menjadi 2,14 m/s. Penggunaan Q20 sebagai debit banjir rencana dalam rencana normalisasi dan pembangunan tanggul Sungai Rongkong dinilai terlalu besar karena menyebabkan biaya konstruksi menjadi sangat mahal. Direkomendasikan untuk menggunakan Q10 sesuai dengan peraturan Kementerian Pekerjaan Umum dan Perumahan Rakyat yang menyatakan bahwa desain banjir untuk tanggul sungai di dekat wilayah ibukota kabupaten/kota harus dapat melewati debit banjir Q10 – Q20. Selain itu juga perlu dilakukan kajian desain terhadap rencana normalisasi dan konstruksi tanggul. Keywords: Pengendalian banjir, morfologi sungai, pemodelan hidraulik, HEC-HMS, HEC-RAS